PENGEMBANGAN E-MAJALAH KIMIA BERBANTUAN KIMIA KOMPUTASI: STUDI INHIBITOR KOROSI MINYAK PALA (MYRISTICA FRAGRANS) PADA TEMBAGA - Gesti Maharani; Saprizal Hadisaputra; Ermia Hidayanti (Chemistry Education Practice, 2026)
This study aims to develop a chemistry e-magazine, assisted by computational chemistry, as a learning supplement for redox reaction material and to determine its validity based on expert assessment. This study uses a mixed-methods approach that combines qualitative data (interviews with teachers and students, descriptions of the development process, and validator input) and quantitative data (student needs questionnaires and Aiken's V index). The development design uses the 4D model (define, design, develop, disseminate), limited to the development stage. The developed e-magazine contains redox reaction material contextualized with the phenomenon of copper corrosion, a study of nutmeg (Myristica fragrans) as a green corrosion inhibitor, DFT-based computational chemistry data (HOMO, LUMO, and energy gap parameters), as well as adsorption values from Monte Carlo simulations on the Cu(111) surface Validation was carried out by three experts using an assessment sheet analyzed with Aiken's V index. The results showed an average V value of 0.84 (very valid), with coverage of graphics (0.85), content feasibility (0.82), presentation feasibility (0.89), and language (0.87). The e-magazine was deemed suitable for use as a supplementary learning resource for chemistry on redox reactions.